Evaluation of the Effectiveness of Post-Natural Disaster Management: A Case Study at the Bima City Regional Disaster Management Agency - Adilansyah, Adilansyah; Hendra, Hendra; Junaidin, Junaidin; Lutfi, Muhamad; Rizkiani, Firliah (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Regional Disaster Management Agency. This type of research is qualitative descriptive research. The data collection techniques used are observation, interviews, and documentation. The analysis technique is qualitative descriptive analysis, which starts from data reduction, data display, and verification and conclusions. The results of this study that facing the risks and impacts of natural disasters in Bima City, this study provides deep insights related to the implementation of post-disaster management by the Regional Disaster Management Agency (BPBD). Various findings and research results create an important foundation for understanding the challenges and opportunities faced in efforts to improve Bima City's resilience to natural disasters. The importance of synergy between local governments, the private sector, and communities is the main focus in building community resilience. Increased awareness, skills, and collaboration between agencies are key to success in minimizing risks and mitigating disaster impacts. By strengthening the post-disaster management system, Bima City can face a more resilient, responsive, and able to maintain the security and welfare of its people. By continuously improving understanding and implementing effective strategies, Bima City has the potential to become an example in building a safe and resilient city against the threat of natural disasters.